Organisational Context Factors Shaping Tanzanian LGAs' Intention to Adopt Innovative Financing Instruments: Financial Advice Moderates - Marko Mwita Imori; Pendo Shukrani Kasoga; Chirongo Moses Keregero (SEISENSE (PRIVATE) LIMITED, 2026)
Purpose: This study uses the TOE framework to examine how organisational factors influence the intention to adopt innovative financing instruments (IAIFI) among Tanzanian LGAs and to test whether financial advice moderates these relationships.Design/Methodology: Data from 255 finance officers and decision-makers across 6 Cities and 20 Municipal Councils were collected using a structured questionnaire that covered LGA’s divisions, departments, sections and units. PLS-SEM tested the study's hypotheses.Findings: Results show that financial advice has a significant positive direct effect on IAIFI and also moderates the effects of institutional pressure and organisational culture on IAIFI. Additionally, organisational culture, top management support, and institutional pressure significantly influence IAIFI, whereas organisational legitimacy does not (p > 0.05, t < 1.96). The model explains 65.7% of IAIFI variance.Practical Implications: These findings suggest that Tanzania can accelerate IFI adoption by strengthening advisory support, streamlining approvals, reducing bureaucracy, and building LGA capacity. LGAs should establish IFI task teams with clear roles, timelines and budgets.Originality: This study extends the literature on innovation adoption by identifying financial advice as a key moderator that mitigates the effects of institutional pressure and organisational culture on the IAIFI, thereby addressing a critical gap in public sector financing and innovation.